Psycho-education cum creative imagery: A treatment for complex posttraumatic stress disorder among women victims of child sexual abuse - Thennattil, Mercy (Animo Repository, 2005)
The study explored the phenomenon of Child Sexual Abuse in women as well as determined the efficacy of psycho-education cum creative imagery in reducing symptoms of Complex Posttraumatic Stress Disorder. The important events in the sessions and the beneficial component of the Intervention package were identified. A combination of descriptive and experimental (N=1 AB with follow up and booster) design was employed. Subjects were women aged 21-29, who were abused as a child (10-16 years old). Convenient and purposive sampling were employed. Initially, 20 were interviewed. Six were chosen as treatment subjects. Instruments used were - Structured Interview for Disorders of Extreme Stress, Important Events Questionnaire, Interview guide and Reports of observers. Descriptive statistics and content analysis were utilized in data analysis. Results indicate that victims showed symptoms in CPTSD domains on Affect and Impulse regulation, Attention or Consciousness, Self-Perception, Relationship with Others, Somatization and Systems of Meaning. After treatment, clinically significant improvement was noticed in Self-perception, Systems of Meaning and other domains. Beneficial components of intervention were psycho-education, creative imagery and relaxation. Consideration of personal meanings of the experience, resolution of negative emotions and strengthening of life-tasks in a culturally sensitive way must be part of posttrauma treatment.